Prevalence rate of left ventricular hypertrophy and the burden of arrhythmias among hypertensive patients attending Jinja regional referral hospital, eastern Uganda - Hussein, Mustafe; Muyinda, Asad; Olet, Stephen Charles; Hersi, Abshir Mohamoud; Said, Abdirahman Ibrahim; Elmi, Hassan Sh Abdirahman (Current problems in cardiology, 2024)
In Uganda, hypertension is an escalating health issue, but there is limited specific data regarding the prevalence of left ventricular hypertrophy (LVH) among hypertensive patients in eastern Uganda. This study aimed to establish the prevalence of LVH among hypertensive patients at Jinja Regional Referral Hospital. A cross-sectional study conducted at the hospital enrolled 323 participants using convenience sampling. The results revealed a prevalence rate of 19.50 % for LVH, primarily observed in male participants and younger age groups (25-35 years). Furthermore, the study found a low incidence of associated cardiac arrhythmia, with only 1.59 % of participants having atrial fibrillation. These findings indicate a relatively low burden of LVH and arrhythmia in this population, emphasizing the importance of continued efforts in hypertension management and LVH prevention. Further research and interventions are necessary to mitigate the impact of hypertension-related complications in the eastern region of Uganda.
Keywords: Burden; Humans; lidé středního věku; Hypertension; prevalence; Female; rizikové faktory; mladý dospělý; dospělí; Aged; Left ventricular hypertrophy; Hypertrophy, Left Ventricular; hypertrofie levé komory srdeční; senioři; lidé; Adult; Referral and Consultation; ženské pohlaví; Male; Middle Aged; hypertenze; srdeční arytmie; incidence; Incidence; konziliární vyšetření a konzultace; Uganda; Cardiac arrhythmia; Cross-Sectional Studies; Young Adult; Prevalence; Arrhythmias, Cardiac; mužské pohlaví; průřezové studie; Risk Factors